Molten steel container water-supply mouth stack - SHUNWANG LI (2006)
The invention relates to ladle water-gap pile device for demolition. Wherein, fixing a positioning plate with fixed sheath on bracket; there are 2-6 locating pins with one end fixed on the said plate and another end removable fixed with chuck that covers on the said sheath; the stay bar has one end clamped by chuck and another end with opening slot; there is a drag bar in the sheath with one end with screw and nut leaned against the said plate and another end fixed of small tie with conical surface leaned against the edge rounding end of stay bar; wherein, rotating the nut, the drag bar can move opposite to bracket. This invention not only decreases the labor strength with well work environment, but also has high efficiency without danger and with low cost.